Mobile DNA III 2015
DOI: 10.1128/9781555819217.ch33
|View full text |Cite
|
Sign up to set email alerts
|

P Transposable Elements in Drosophila and other Eukaryotic Organisms

Abstract: P transposable elements were discovered in Drosophila as the causative agents of a syndrome of genetic traits called hybrid dysgenesis. Hybrid dysgenesis exhibits a unique pattern of maternal inheritance linked to the germline-specific small RNA piwi-interacting (piRNA) pathway. The use of P transposable elements as vectors for gene transfer and as genetic tools revolutionized the field of Drosophila molecular genetics. P element transposons have served as a useful model to investigate mechanisms of cut-and-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 155 publications
0
35
0
Order By: Relevance
“…A classic example is the Drosophila P element, whose transposase open reading frame (ORF) is interrupted by an intron that is spliced only in the germline, preventing P-element mobility in the soma, where only prematurely truncated inhibitory transposase is produced (Laski et al 1986). It appears that this regulatory switch was evolved through the gain of sequence elements within the transposon that recruit somatically expressed splicing inhibiting factors (for review, see Majumdar and Rio 2015). A recent study adds another layer of intricacy by implicating the piRNA pathway in repressing the splicing of this intron in the germ cells through piRNA-mediated chromatin changes within the P element (Teixeira et al 2017).…”
Section: Self-regulatory Mechanismsmentioning
confidence: 99%
“…A classic example is the Drosophila P element, whose transposase open reading frame (ORF) is interrupted by an intron that is spliced only in the germline, preventing P-element mobility in the soma, where only prematurely truncated inhibitory transposase is produced (Laski et al 1986). It appears that this regulatory switch was evolved through the gain of sequence elements within the transposon that recruit somatically expressed splicing inhibiting factors (for review, see Majumdar and Rio 2015). A recent study adds another layer of intricacy by implicating the piRNA pathway in repressing the splicing of this intron in the germ cells through piRNA-mediated chromatin changes within the P element (Teixeira et al 2017).…”
Section: Self-regulatory Mechanismsmentioning
confidence: 99%
“…IR events have been reported to be frequently found in mammals and have been shown to play crucial roles for the normal functioning of the organism and in disease in eukaryotes (34,35). For example, tissue-specific IR of the Drosophila P-element transposase pre-mRNA underlies the restriction of transposon activity to germ-line tissues (36,37). Recently, a bioinformatics study reported that widespread retained introns were associated with various cancer types compared with matched normal tissues (38).…”
Section: Wang and Riomentioning
confidence: 99%
“…Hence, we explored the possibility of an insertion site bias inherent to our StanEx 1 P-element construct. We generated a position frequency matrix (PFM, Figure 3A) and sequence logo of the 14 bp P-element insertion site motif (Majumdar and Rio, 2014) using 128 unique StanEx 1 insertions that were characterized by insertion site sequencing with single nucleotide precision on the 5' and 3' ends (Crooks et al, 2004; Figure 3B). This StanEx 1 PFM was individually compared to PFMs of the P elements EPgy2 (n=3112), GT1…”
Section: Selected Tissue Expression Of Lexa In the Stanex Collectionmentioning
confidence: 99%
“…A KP element is a non-autonomous P-element with intact inverted repeats, whose transposase-encoding exons 2-4 contain deletions. These deletions produce an (ORF) frame that encodes a type II repressor instead of functional transposase (Black et al, 1987;Rio, 1990;Majumdar and Rio, 2014;Kellerher, 2016), permitting KP element mobilization only when transposase is provided in trans. Thus, an interaction of a KP-element with the StanEx Pelement in the StanEx 1 starter strain could underlie the observed repeated integration of StanEx P-element into 88B4-6.…”
Section: An Unrecognized Kp Element In Thementioning
confidence: 99%